Dupilumab therapy of atopic dermatitis of the elderly: a multicentre, real‐life study. (19th January 2021) - Patruno, C.; Napolitano, M.; Argenziano, G.; Peris, K.; Ortoncelli, M.; Girolomoni, G.; Offidani, A.; Ferrucci, S.M.; Amoruso, G.F.; Rossi, M.; Stingeni, L.; Malara, G.; et al.
Abstract: Background: Treatment of moderate‐to‐severe atopic dermatitis (AD) in the elderly may be challenging, due to side‐effects of traditional anti‐inflammatory drugs and to comorbidities often found in this age group. Furthermore, efficacy and safety of innovative drugs such as dupilumab are not yet well known. Objectives: A multicentre retrospective, observational, real‐life study on the efficacy and safety of dupilumab was conducted in a group of patients aged ≥65 years and affected by severe AD. Their main clinical features were also examined. Methods: Data of elderly patients with severe (EASI ≥24) AD treated with dupilumab at label dosage for 16 weeks were retrospectively collected. Treatment outcome was assessed by comparing objective (EASI) and subjective (P‐NRS, S‐NRS and DLQI) scores at baseline and after 16 weeks of treatment. Results: Two hundred and seventy‐six patients were enrolled in the study. They represented 11.37% of all patients with severe AD. Flexural eczema was the most frequent clinical phenotype, followed by prurigo nodularis. The coexistence of more than one phenotype was found in 63/276 (22.82%) subjects. Data on the 16‐week treatment with dupilumab were available for 253 (91.67%) patients. Efficacy of dupilumab was demonstrated by a significant reduction of all the scores. No statistically significant difference regarding efficacy was found in elderly patients when compared to the group of our AD patients aged 18–64 years, treated with dupilumab over the same period. Furthermore, only 18 (6.52%) patients discontinued the drug due to inefficacy. Sixty‐one (22.51%) patients reported adverse events, conjunctivitis and flushing being the most frequent. One (0.36%) patient only discontinued dupilumab due to an adverse event. Conclusions: Therapy with dupilumab led to a significant improvement of AD over a 16‐week treatment period, with a good safety profile. Therefore, dupilumab could be considered as an efficacious and safe treatment for AD also in the elderly.